1985
DOI: 10.1002/hep.1840050616
|View full text |Cite
|
Sign up to set email alerts
|

Halothane Hepatitis Without Halothane: Role of Inapparent Circuit Contamination and Its Prevention

Abstract: Halothane and other halogenated anesthetic agents are liquids which are highly soluble in rubber and plastic materials widely used as components of anesthesia machines. These agents must be administered using machines equipped with vaporizers. We report a patient with a past history of halothane hepatitis in whom recurrence was suspected despite the fact that halothane had been avoided purposely during the subsequent operation. Circumstances led us to believe that inapparent circuit contamination of vaporizer-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…55 Whereas with morphine, which has a low fat solubility, a proportionally higher amount of morphine would cross into the brain of a newborn compared to an older child, simply because of the immaturity of the blood brain barrier. 56 Studies have shown that the peak pharmacodynamic effects of benzodiazepines are also directly proportional to fat solubility; the peak EEG effect of diazepam is nearly three times faster than that of midazolam. 57,58 A common misconception is the reverse, i.e.…”
Section: Pharmacologic Considerationsmentioning
confidence: 99%
“…55 Whereas with morphine, which has a low fat solubility, a proportionally higher amount of morphine would cross into the brain of a newborn compared to an older child, simply because of the immaturity of the blood brain barrier. 56 Studies have shown that the peak pharmacodynamic effects of benzodiazepines are also directly proportional to fat solubility; the peak EEG effect of diazepam is nearly three times faster than that of midazolam. 57,58 A common misconception is the reverse, i.e.…”
Section: Pharmacologic Considerationsmentioning
confidence: 99%
“…For the patient who has had unexplained jaundice following a previous halothane anaesthetic, it is crucial that a halothane-free anaesthetic machine is used, since it has been shown that sufficient amounts of the drug can be released from the rubber tubing when another anaesthetic agent is used to sensitise such patients (Varma et al 1985). Current evidence also suggests that other halogenated anaesthetics should not be used.…”
Section: Reduction Of the Incidence Of Halothane Hepatitismentioning
confidence: 99%
“…Other factors suggestive of possible patients at risk include those who are female and obese, with a history of allergy or eczema. In this context it should be realized that enough halothane may contaminate the conventional anaesthetic machine so that when a 'non-halothane' anaesthetic is given, enough halothane may be released from the tubing to cause a hepatitis (9). Thus ideally, a halothane-free machine should be used in such patients.…”
mentioning
confidence: 99%